Telecommunications Regulation Handbook : Tenth Anniversary Edition - Blackman, Colin; Srivastava, Lara (World Bank and the International Telecommunication Union, Washington, DC, 2013)
Communications are an essential means for reaching the, bottom of the Pyramid, and enabling individuals to reduce poverty and improve the quality of their lives. We currently live in a world in which more Africans have access to a mobile phone than to any other utility or infrastructure service. This widespread technological dissemination creates new opportunities across all segments of society, but also presents new challenges requiring adaptable strategies. Today's communications landscape is vastly different from the environment in which we developed the first telecommunications regulation handbook ten years ago. Competitive and open communications markets have created opportunities in countries that previously lagged behind. Competitively priced and technologically varied service offerings have allowed businesses to compete and thrive globally. However, there are still serious market gaps (such as providing widespread high speed broadband services at affordable prices and connectivity to remote areas), that, when coupled with evolving and converging technologies, pose challenges to policymakers and regulators. This new edition of the telecommunications regulation handbook captures the new market and regulatory strategies to optimize investment in broadband networks and Information and Communication Technology, or ICT services. As the following chapters show, many of the evolutionary and revolutionary changes in regulation that made possible the mobile miracle of connecting 5 billion users worldwide with access to ICTs, as well as over a billion fixed and mobile broadband subscribers, are still valid today. But for markets to truly flourish, regulators also need new, inspired regulatory approaches that are as innovative as the technologies they regulate.